2021
DOI: 10.1021/acs.est.1c04323
|View full text |Cite
|
Sign up to set email alerts
|

Disinfection Byproduct Recovery during Extraction and Concentration in Preparation for Chemical Analyses or Toxicity Assays

Abstract: Over 700 disinfection byproducts (DBPs) have been identified, but they account for only ∼30% of total organic halogen (TOX). Extracting disinfected water is necessary to assess the overall toxicity of both known and unknown DBPs. Commonly used DBP extraction methods include liquid–liquid extraction (LLE) and solid-phase extraction (SPE), which may use either XAD resins or other polymeric sorbents. With few exceptions, DBP recoveries have not been quantified. We compared recoveries by LLE, XAD resins, and a mix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 46 publications
0
23
0
Order By: Relevance
“…GC × GC-TOF-MS provides high separation resolution and accurate mass information, allowing a potent characterization of unknown compounds in complex environmental samples. It should be noted that SPE was used for isolation and enrichment in the current study, and only halo-DBPs that can be adsorbed by cartridge materials and desorbed by the organic solvent were analyzed by mass spectrometry. , Analytes of high volatility were removed by a nitrogen evaporator, and nonvolatile analytes were also excluded due to the limitation of GC injector. Hence, when discussing the results from GC × GC-TOF-MS, the conditions of sample preparation and analysis should be considered, as the current study mainly characterized the HLB extractable analytes, which did not reflect all halo-DBPs in chlorinated waters.…”
Section: Resultsmentioning
confidence: 99%
“…GC × GC-TOF-MS provides high separation resolution and accurate mass information, allowing a potent characterization of unknown compounds in complex environmental samples. It should be noted that SPE was used for isolation and enrichment in the current study, and only halo-DBPs that can be adsorbed by cartridge materials and desorbed by the organic solvent were analyzed by mass spectrometry. , Analytes of high volatility were removed by a nitrogen evaporator, and nonvolatile analytes were also excluded due to the limitation of GC injector. Hence, when discussing the results from GC × GC-TOF-MS, the conditions of sample preparation and analysis should be considered, as the current study mainly characterized the HLB extractable analytes, which did not reflect all halo-DBPs in chlorinated waters.…”
Section: Resultsmentioning
confidence: 99%
“…We employed an EPA-defined XAD extraction protocol for this study . A recent study discovered that several DBPs measured in this study are lost or incompletely recovered during XAD resin extraction and concentration protocols used to prepare samples for bioassays . For example, THMs and trihalogenated HAAs have negligible recoveries using XAD, and other (semi-)­volatile DBPs have lower recoveries using XAD (<30%) than LLE or solid phase extraction (30–60%).…”
Section: Resultsmentioning
confidence: 99%
“…61 A recent study discovered that several DBPs measured in this study are lost or incompletely recovered during XAD resin extraction and concentration protocols used to prepare samples for bioassays. 91 For example, THMs and trihalogenated HAAs have negligible recoveries using XAD, and other (semi-)volatile DBPs have lower recoveries using XAD (<30%) than LLE or solid phase extraction (30−60%). This means that the bioassays may be mostly measuring the cytotoxic contributions of the non-volatile and uncharacterized fraction of DBPs.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…Therefore, the exclusion of unknown I-DBPs can underestimate the toxicity of disinfected waters. On the other hand, it was recently reported that the recoveries of known DBPs during XAD adsorption and solvent exchange processes prior to bioassays are <20% . Therefore, it is likely that the toxicity of bulk extract by bioassays only reflects the uncharacterized fraction of DBPs, which can also lead to discrepancies between calculated and experimentally measured toxicity.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, it was recently reported that the recoveries of known DBPs during XAD adsorption and solvent exchange processes prior to bioassays are <20%. 91 Therefore, it is likely that the toxicity of bulk extract by bioassays only reflects the uncharacterized fraction of DBPs, which can also lead to discrepancies between calculated and experimentally measured toxicity. The CTI value of chloraminated water by preformed NH 2 Cl was significantly higher than the calculated additive cytotoxicity.…”
Section: ■ Results and Discussionmentioning
confidence: 99%